KOMPARASI PERMENDIKBUD NOMOR 137 TAHUN 2014 DENGAN PERMENDIKNAS NOMOR 58 TAHUN 2009 DALAM PEMBELAJARAN PAUD - M Fadlillah (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2016)
The implementation of early childhood learning in Indonesia prior to the issuance Permendikbud No. 137 of 2014 is referred to and guided by the Permendiknas 58 Year 2009. Then after Permendikbud No 137 of 2014 is set, then Permendiknas 58 The year 2009 is no longer valid and can not be used as guidelines in the implementation of early childhood education. Permendikbud No. 137 of 2014 is a manifestation of the implementation of Curriculum 2013, while Permendiknas 58 The year 2009 was a manifestation of the Education Unit Level Curriculum (SBC). From a technical point of these two regulations is different, but in terms of content or meaning in general have similarities. Nonetheless, Permendikbud No. 137 of 2014 is designed to melengkapai and enhance Permendiknas 58 Year 2009 on Early Childhood Education Standards